The knowledge and behavior levels of the students taking disaster awareness training: The example of Tekirda province, Turkey (Nepal Journal of Environmental Science, 2017)
The aim of this study is to determine the knowledge, skill and behavior levels of the individuals, suffering from a disaster, in terms of issues such as survival, finding a safe place, evacuation, first aid, and search and operations as of the first hours following the disaster. Within this scope, 128 students taking disaster awareness training in Vocational School of Health Services in Namık Kemal University of Turkey agreed to participate in this study. The data collection form was prepared by using the preceding studies in literature. The data were analyzed with “SPSS for Windows 15.0”' package program. Variance analysis, student’s t-test, chi-square test and Pearson correlation test were performed for statistical analyses. The results in which P values were p